Rhodium-catalyzed cycloaddition of carbonyl ylides for the synthesis of spiro[furo[2, 3-a]xanthene-2, 3′-indolin]-2′-one scaffolds. Issue 56 (24th May 2016) - Reddy, B. V. Subba; Reddy, E. Pravardhan; Sridhar, B.; Rao, Y. Jayaprakash
Abstract : Rh(ii )-catalyzed cycloaddition of 3-diazooxindoles with 2-methyl-2-(4-methylpent-3-en-1-yl)-2 H -chromene-3-carbaldehydes has been developed to produce tetrahydro-3 H, 4 H -spiro[furo[2, 3- a ]xanthene-2, 3′-indolin]-2′-ones in good yields. Abstract : An intramolecular cycloaddition of oxonium ylides generated from 3-diazooxindole and a bifunctional substrate i.e. 2-methyl-2-(4-methylpent-3-en-1-yl)-2 H -chromene-3-carbaldehyde has been achieved using 5 mol% of Rh2 (OAc)4 to produce highly substituted 3, 3, 5a-trimethyl-3a, 5, 5a, 11b-tetrahydro-3 H, 4 H -spiro[furo[2, 3- a ]xanthene-2, 3′-indolin]-2′-ones in good yields with high diastereoselectivity. This is the first example of the synthesis of biologically relavant polycyclic frameworks from readily accessible precursors.